The Anthropocene: Thought styles, controversies and their expansions. A review - Hafner, Robert (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
This review article uses the 2000 appearance of the Anthropocene as a conceptual anchor to further explore and embed thought styles on human-environment relations. In so doing, three main points are made: First, the Anthropocene is nothing new. Pre-ideas of a proto-Anthropocene, i.e. the importance of humans in human-environment relation have been previously explored. Second, while the first half of the 2000s was predominantly of stratigraphic concerns, the second half showed controversies between normative embeddings of good, bad and alternative thought styles on the Anthropocene. Third, with a scientific lag of approximate 15 years, multiplicities of alternative wordings have made their way as thought style expansions on the Anthropocene, re-framing and -branding existing thought styles (in e.g. ecomodernist, critical feminist, political ecologist fashion) in an attempt to achieve virality with other, more concrete wordings of the Anthropocene.